Economic Analysis of the European Healthcare Burden of Sternal-Wound Infections Following Coronary Artery Bypass Graft - Blüher, Maximilian; Brandt, Dominique; Lankiewicz, Julie; Mallow, Peter J.; Saunders, Rhodri (Frontiers in Public Health, 2020)
Background: Sternal wound infections (SWIs) can be some of the most complex surgical-site infections (SSIs) and pose a considerable risk following coronary artery bypass graft surgery (CABG). Objective: To capture the cost burden of SWIs following CABG across European countries. Methods: We modeled a standardized care pathway for CABG, starting at the point of surgery and extending to 1-year post surgery. The Markov model captures the incidence and cost of an SWI (deep or superficial SWIs). The cost burden is calculated from a hospital perspective such that the main inputs relating to costs were intensive-care-unit (ICU) and general-ward (GW) days. Outpatient care, not in the hospital setting, has no cost in this analysis. Model input parameters were taken from Eurostat and a review of published, peer-reviewed literature. European countries were included in this analysis when values for 50% of the required input parameters per country were identified. Missing data points were interpolated from available data. The robustness of results was assessed via probabilistic sensitivity analysis. Results: Full required input data were available for 8 European countries; a further 18 countries had sufficient data for analysis. The median (interquartile range) for SWI incidence across the 26 countries was 3.9% (2.9–5.6%). The total burden for all 26 countries of SWIs after CABG was €170.8 million. These costs were made up of 25,751 additional ICU days, 137,588 additional GW days, and 7,704 readmissions. The mean cost of an SWI ranged from €8,924 in Poland to €21,321 in Denmark. Relative to the costs of post-CABG care without an SWI complication, the incremental cost of an SWI was highest in Greece (24.9% increase) and lowest in the UK (3.8% increase) with a median (interquartile range) of 12% (10–16%) across all 26 countries. Conclusions: SWIs following CABG present a considerable burden to healthcare budgets.